Evaluación de la incorporación de remolacha en la etapa de cocción y fermentación del proceso productivo de cerveza artesanal tipo Ale (2021)
In the following degree work, tests were carried out to evaluate the use of Beta Vulgaris (Beet) as an adjunct ingredient for the production of craft beer, this is in order to innovate in the field of craft brewery in Colombia and in this way expand the group of raw materials that can be used to prepare this type of drink. For this, a total of 8 batches of beer of 5 L each were made, in which the beet was added in the form of juice. This in turn was pretreated to eliminate microorganisms that could be present and adversely affect the process. The juice was added in 2 separate parts of the process (cooking and fermentation) and in different concentrations based on the malt mass that was added (15% w / v and 30% w / v).